Influence of graphene addition and sintering temperature on physical properties of Si3N4 matrix composites. (June 2016) - Cygan, Tomasz; Wozniak, Jaroslaw; Kostecki, Marek; Adamczyk-Cieslak, Boguslawa; Olszyna, Andrzej
Abstract: The Si3 N4 -graphene composites (1 wt% addition of graphene) were manufactured using powder metallurgy and consolidated using the Spark Plasma Sintering (SPS) method. In order to achieve composites with high mechanical properties, optimisation of a Si3 N4 and Si3 N4 -graphene sintering temperatures were carried on for five and four different sintering temperatures respectively. Obtained samples were characterised by measurements of their density, hardness, fracture toughness and Young's modulus. Qualitative and quantitative phase composition was analysed by XRD diffraction. Microstructure analysis of sinters was also performed using Scanning Electron Microscopy (SEM). The highest relative density (99.31% and 99.32%) and fracture toughness (KIC = 6.0 MPa ∗ m 0.5 ) was measured for samples sintered at 1650 °C and 1700 °C respectively, for Si3 N4 and Si3 N4 –Gn composite. That shows no increase of fracture toughness between pure silicon nitride sinter and composite with 1% wt of graphene. Furthermore, XRD results showing 33% less of β grains in Si3 N4 –Gn composite compared to pure Si3 N4 sample, proving that graphene stabilise the α phase in silicon nitride. Graphical abstract: Highlights: SPS method allows obtaining samples with high relative density. XRD analysis shows higher amount of β phase in Si3 N4 with temperature increase. SEM microstructures show increasing ratio of α–β with temperature growth. Optimal sintering temperature for silicon nitride using SPS is 1650 °C. Graphene stabilises α phase in silicon nitride.